'I Have an Empty Head on Love': The Theme of Love in Derrida, or Derrida and the Literary Space. Issue 2 (December 2018) - Ben-Naftali, Michal
Abstract : The essay examines several scenes of love in deconstruction, in an attempt to understand why Derrida claims to have 'an empty head on love in general', as he says in a film dedicated to his work. Beginning with 'Romeo and Juliet' up to Abraham's sacrificial responsibility, the essay aims to interpret Derrida's withdrawal to silence about love as enacting the erotic literary space of his own writing.